The Impact of Perceived Value of Uniqlo and Disney in the Purchase Intention Mediated by Attitude Toward UT Disney - Natasha Raphaella Halim; Prasetya Admaja (iBuss Management, 2019)
Fast fashion retail, which focuses on fast-pace retailing and affordable clothing, stands out as one of the greatest disruptors in fashion industry. One of the top three fast fashion retail brand is Uniqlo. It has an ambitious plan to become number one fast fashion retail brand in the world. One of its strategy to aim its goal is co-branding. The researchers focus on the co-branding collaboration between Uniqlo and Disney. The researchers want to examine the factors that influence purchase intention on the co-branded product which is UT Disney. Do perceived value of Uniqlo and Disney affect purchase intention on UT Disney?  Does attitude toward UT Disney mediates perceived value of Uniqlo and Disney toward purchase intention on UT Disney?The researchers have collected 89 valid data from respondents using simple random sampling method. The data collected are then analyzed with multiple linear regression and Sobel test. The result of the analysis concluded that perceived value of Uniqlo and Disney significantly influence purchase intention on UT Disney. Moreover, there is also mediation effect of attitude toward UT Disney between perceived value of Uniqlo and Disney toward purchase intention on UT Disney. Keywords:Perceived Value, Attitude toward UT Disney, Purchase Intention, Uniqlo, Disney, UT Disney